Shear behavior of a perfobond strip with steel fiber-reinforced mortar in a condition without surrounding reinforcements - Hai, Nguyen Minh; Nakajima, Akinori; Fujikura, Shuichi; Murayama, Takara; Mori, Misaki (Materials and structures, 2020)
To sufficiently transmit the shear force of a perfobond strip shear connector in steel–concrete hybrid structures, the arrangement of the surrounding reinforcements is essential to improve the restraining effect around the perfobond strip. However, in cases of joint structures with small dimensions and rush work on site, because the arrangement of reinforcements in the joint is challenging, steel fiber-reinforced mortar (SFRM) can be used along with a perfobond strip to improve the restraining effect around the perfobond strip. This study investigates the shear behavior of a perfobond strip that uses SFRM without surrounding reinforcements. Push-out tests were conducted focusing on the effect of steel fibers inside the SFRM, SFRM compressive strength, perforation diameter, and dimensions of the mortar block around the perfobond strip. Findings of the study confirmed that the steel fibers inside the mortar contribute to the restraining effect around the perfobond strip, thus preventing a rapid drop in the shear force beyond the shear capacity of the perfobond strip. The shear capacity of the perfobond strip combined with SFRM increased with the perforation diameter, SFRM compressive strength, and dimensions of the mortar block around the perfobond strip. Several shear capacity evaluation equations proposed in previous studies are not applicable for evaluating the shear capacity of the perfobond strip that uses SFRM without surrounding reinforcements. Here, the shear capacity of the perfobond strip can be evaluated by considering the correlation between the experimental parameters of this study, but more test data are required.